Competition for natural resources in California's Sierra Nevada - Frank Mittelbach; Dennis Wambem (European Regional Science Association (ERSA), 2002)
This paper analyzes the impact of competitive forces on natural resources in California's Sierra Nevada and neighboring areas. This hilly and mountainous region extends for more than 700 kilometers from north and south in the eastern part of California. It comprises an area of 80,000 square kilometers, rich in resources, including 50 percent of the State's water supply, extensive but declining timber industries and mineral extraction, a fragile, distinct wildlife and high amenity recreational opportunities for visitors from the United States and abroad. Economic activities substantially based on natural resource extraction and direct or indirect exports to other areas of California or the rest of the world are supplemented by recent developments which consume significant land and other resources within the region. They include exurban growth encompassing long distance commutes by Sierra Nevada residents who work in the San Francisco Bay area, the Sacramento metropolis or southern California. The expansion of second home and retirement communities, plus growth of the built environment serving visitors (or workers in visitor industries), challenges the quality of the local environment as well as production and transport of natural resources to other regions. More recently, developments in communication and information systems have facilitated work-at-home by skilled professionals in the high amenity Sierra Nevada, who also demand sophisticated locally produced business and personal services. One consequence in recent years has been the relatively rapid population and housing growth compared to the State's coastal regions and the adjacent Central Valley with its burgeoning agricultural industries serving national and world wide demands. The paper documents the impact of growing resource competition in the region and the emergent conflicts among the various interests and groups. In the process the variety of measures proposed and implemented to maintain the region's amenities and exports are examined and their effectiveness is evaluated. These include: 1. Approaches to regulate and control the water supply to benefit California urban and rural areas within the region and elsewhere; 2. measures limiting logging to preserve the watershed and natural environment; 3. curbs or moratoria on land development and; 4. direct or indirect subsidies with differential impacts frequently serving special interests. Particular attention is directed to scrutiny of these measures applying concepts and theories from welfare economics.
Keywords: 330